Regulation of Nuclear Factor-kappaB Function by O-GlcNAcylation in Inflammation and Cancer - Liu, Angela Rose; Ramakrishnan, Parameswaran (Frontiers in Cell and Developmental Biology, 2021)
NF-kB is a pleiotropic, evolutionarily conserved transcription factor family that plays a central role in regulating immune responses, inflammation, cell survival, and apoptosis. Great strides have been made in the past three decades to understand the role of NF-kB in physiological and pathological conditions. Carcinogenesis is associated with constitutive activation of NF-kB that promotes tumor cell proliferation, angiogenesis, and apoptosis evasion. NF-kB is ubiquitously expressed, however its activity is under tight regulation by inhibitors of the pathway and through multiple posttranslational modifications. O-GlcNAcylation is a dynamic posttranslational modification that controls NF-kB-dependent transactivation. O-GlcNAcylation acts as a nutrient-dependent rheostat of cellular signaling. Increased uptake of glucose and glutamine by cancer cells enhances NF-kB O-GlcNAcylation. Growing evidence indicates that O-GlcNAcylation of NF-kB is a key molecular mechanism that regulates cancer cell proliferation, survival and metastasis and acts as link between inflammation and cancer. In this review, we are attempting to summarize the current understanding of the cohesive role of NF-kB O-GlcNAcylation in inflammation and cancer.